The association between early maladaptive schemas and romantic relationship satisfaction - Kover, Lili; Szollosi, Gergo Jozsef; Frecska, Ede; Bugan, Antal; Berecz, Roland; Egerhazi, Aniko (Frontiers in Psychology, 2024)
IntroductionRelationship dynamics could be shaped by schemas, and relationship satisfaction could be depend on how couples perceive each other through these schemas. The main aim of this study was to assess how early maladaptive schemas are related to relationship satisfaction for both males and females in a relationship, by highlighting factors that contribute to relationship satisfaction, with a particular focus on the interaction of schemas between males and females.MethodsThe study involved a total of healthy 47 different-gender couples. Participants completed the Personal Assessment of Intimacy in Relationship (PAIR) and Young’s Schema questionnaires. Actor-partner interdependence models (APIM) were created to assess which factors contributed to satisfaction.ResultsOur study identifies sex differences in early maladaptive schemas, revealing complex interactions within romantic relationships. Strong associations were observed between both sexes’ maladaptive schemas, suggesting mutual influence. The emotional deprivation schema is associated with reduced satisfaction for both partners. For females, the abandonment schema is linked to decreased both their own and their partner’s satisfaction, while the mistrust/abuse schema is related to lower satisfaction in the male partner. Social isolation and defectiveness/shame schemas are associated with lower female satisfaction but do not appear to affect their partners, whereas male satisfaction is reduced by vulnerability to harm. Schemas such as failure to achieve, dependence/incompetence and enmeshment show little association with relationship satisfaction. Approval-seeking schema is linked to reduced female satisfaction, and negativity/pessimism is associated with reduced male satisfaction.DiscussionOur research provides a nuanced insight into the interactions between partners’ schemas, thus improving the understanding of how maladaptive schemas may contribute to relationship outcomes.